IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAM AT PT ANUGERAH LANGKAT MAKMUR - Chiquitita Qinthar Azura; Iwan Setiawan (Agricultural Socio-Economics Journal, 2022)
Corporate social responsibility (CSR) is a form of management defined by an ethical and transparent relationship between the company and all stakeholders (relevant parties) in the form of community development, environmental and cultural preservation for future generations, diversity and the promotion of reducing social problems. As a matter of fact, the community feel cared for through PT Anugerah Langkat Makmur's (PT ALAM) CSR activities, whereas the company only produces semi-finished products or has no direct relationship with end consumers. Qualitative designed research using case study methods aims to determine the types and implementation of CSR programs at PT ALAM. Primary data collection was collected with in-depth observation and interview techniques, while secondary data was collected through desk study from Public Relation of PT ALAM. The collected data was analyzed descriptionally. The results show that PT ALAM has implemented corporate social marketing, corporate philanthropy, and socially responsible business practice program. CSR is implemented every year and has been internalized in its business structure. PT ALAM has implemented CSR programs in the form of education, construction of facilities and infrastructure, as well as socio-cultural and religious.